Impact of Academic Rank on Organizational Commitment - Al-Rfou, Ahmad Nahar (Journal of Asian Business Strategy, 2012)
Academic staffs are the backbone of any university. Thus, building Organizational Commitment (OC) among them is a necessity for any university to be effective. The current study investigates the impact of academic rank (i.e., professor, associate professor and assistant professor) on OC (i.e., affective commitment, continuance commitment and normative commitment) for academics staff at Tafila Technical University (TTU). Questionnaires of (100) were sent both via email and on hand out to sample from academic staff at TTU, (65) questionnaires were analyzed to achieve the research objective. The results of the study show that the relationship between academic rank and OC is partially accepted. The professors pointed to high level of continuance commitment to maintain their achievements and benefits, while, assistance professors focused on normative commitment and stay at the university to meet their legal obligations towards the university.